2019
DOI: 10.1002/suco.201800204
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on fracture behavior of notched self‐consolidating concrete beam strengthened with off‐axis CFRP sheet

Abstract: In this study, the effects of fiber orientation within the carbon fiber reinforced (CFRP) sheets, on the fracture mode and crack growth of specimens were investigated by constructing five groups of initially notched self‐consolidating concrete beams, and strengthening them with CFRP sheets in the tensile area. Furthermore, the bearing capacity, strain variation along the sheet, crack mouth opening, and the midspan displacement were recorded by varying the height of the beams and the initial notch lengths. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…FRP is a high‐performance composite material, which is composed of certain proportions of fiber material and resin matrix material. Because of the properties of high strength and stiffness‐weight ratio, superior corrosion resistance, and on‐field ease of application, the use of FRP composites as external confinement for concrete structures has received a great deal of attention in the last two decades, 4,5 and it has also been applied to strengthen arch structures for years 6 . The FRP strengthening is effective in improving load‐carrying capacity, decreasing structural deformation, and improving structural stability of masonry arches 7,8 and RC arches 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…FRP is a high‐performance composite material, which is composed of certain proportions of fiber material and resin matrix material. Because of the properties of high strength and stiffness‐weight ratio, superior corrosion resistance, and on‐field ease of application, the use of FRP composites as external confinement for concrete structures has received a great deal of attention in the last two decades, 4,5 and it has also been applied to strengthen arch structures for years 6 . The FRP strengthening is effective in improving load‐carrying capacity, decreasing structural deformation, and improving structural stability of masonry arches 7,8 and RC arches 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been conducted on retrofitting of RC beams. Sangi et al [10] made 35 self-compacting concrete beams and retrofitted them with CFRP sheets in the tensile zone (bottom surface of the beam). Also, numerical simulation was used to investigate the fracture mode and cracks distribution in the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Also, numerical simulation was used to investigate the fracture mode and cracks distribution in the samples. It was indicated that the retrofitted beam with CFRP angle 0° has more capacity *Corresponding Author Email: Sayari_arash@yahoo.com (A. Sayari) in comparison to other specimens [10]. Shadmand et al [11] introduced a proposed method for retrofitting RC beams in which steel-concrete composite jackets containing steel fibers were used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation